Virulence factors of fluconazole-susceptible and fluconazole-resistant Candida albicans after antimicrobial photodynamic therapy - Alves, Fernanda [UNESP]; de Oliveira Mima, Ewerton Garcia [UNESP]; Passador, Renata Caroline Polato [UNESP]; Bagnato, Vanderlei Salvador; Jorge, Janaína Habib [UNESP]; Pavarina, Ana Cláudia [UNESP] (Springer Nature, 2017)
This study evaluated the effects of antimicrobial photodynamic therapy (aPDT) mediated by Photodithazine® (PDZ) and LED light on the virulence factors of fluconazole-susceptible (CaS) and fluconazole-resistant (CaR) Candida albicans. Standardized suspensions of strains were prepared (107), and after 48 h of biofilm formation, these strains were incubated with PDZ (100 mg/L) for 20 min and exposed to LED light (660 nm, 37.5 J/cm2). Additional samples were treated with PDZ or light only, and the control consisted of biofilms that received no treatment. After aPDT, the cells were recovered and the virulence factors were evaluated. To analyze the capacity of adhesion, cells were recovered after aPDT and submitted to the adhesion process in the bottom of a 96-well plate. After this, metabolic activity tests (XTT assay) and cell viability (colony forming units per milliliter, CFU/mL) were applied. To evaluate the biofilm-forming ability after aPDT, the cells recovered were submitted to biofilm formation procedures, and the biofilm formed was evaluated by XTT, CFU/mL, and total biomass (crystal violet) tests. Lastly, the capacity for synthesizing protease and phospholipase enzymes after aPDT was evaluated by fluorimetric tests. Data were analyzed by two- or three-way ANOVA tests (p ≤ 0.05). It was verified that aPDT reduced the viability of both strains, fluconazole-susceptible and fluconazole-resistant C. albicans. It was also observed that the CaR strain had lower susceptibility to the aPDT when compared with the CaS strain. However, regarding the virulence factors evaluated, it was demonstrated that aPDT did not alter the adherence and biofilm formation ability and enzymatic production.
Keywords: Candida albicans; Drug resistance; Photodynamic inactivation; Virulence factors